Effect of ipratropium bromide on mucociliary clearance and pulmonary function in reversible airways obstruction. - Pavia, D (1979)
The effects of (a) regular use for one week and (b) a single dose of a synthetic anticholinergic (ipratropium bromide) on lung mucociliary clearance and as a bronchodilator was ascertained in a controlled, double-blind, cross-over study in 12 patients with reversible airways obstruction (mean increase in FEV after isoprenaline: 17% range 10-50%). Two puffs from a metered dose inhaler of either placebo (propellants only) or drug (40 microgram) were administered four times a day for one week (regular use), and mucociliary clearance was measured, by radioaerosol tracer, at the end of each treatment period and after a control period in which no treatment was given. On the mornings of the measurements after the placebo and drug periods one final dose (single dose) of ipratropium (40 microgram) or placebo was given 2.5 hours before the start of the test. There was no statistically significant difference between the three mean mucociliary clearance curves (control, placebo, and drug) for the group; however, there was a significantly greater penetration towards the periphery of the lung of the tracer in the test after drug administration compared with the other two. This increased penetration was attributed to bronchodilatation caused by the drug. Ipratropium bromide does not appear to impair mucociliary clearance, and it acts an effective bronchodilator.